Electrochemical performance of all-solid-state lithium batteries using inorganic lithium garnets particulate reinforced PEO/LiClO4 electrolyte. (1st November 2017) - Cheng, Samson Ho-Sum; He, Kang-Qiang; Liu, Ying; Zha, Jun-Wei; Kamruzzaman, Md; Ma, Robin Lok-Wang; Dang, Zhi-Min; Li, Robert K.Y.; Chung, C.Y.
Abstract: All-solid-state batteries are proposed to have ultimate safety and higher power and energy densities over conventional lithium ion batteries with liquid electrolytes. The Li ion conductivity and interfacial resistance between electrolyte and electrodes are the major bottleneck of the development of all-solid-state batteries for practical uses. Here, we reported a novel composite electrolyte which is composed of uniform distributed Li ion conducting Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) fillers in PEO/LiClO4 matrix. The EO:Li + ratio of 15:1 is being used to achieve lower interfacial resistance between electrolyte and electrodes through the melting process. The composite electrolyte is fabricated by simple solution casting method, which is more advantageous comparing with high temperature sintering or sol-gel method used in the fabrication of ceramic electrolytes. The composite electrolyte exhibits good Li ion conductivity of 4.8 × 10 −4 Scm −1 at 60 °C and excellent interfacial stability against Li metal. The all-solid-state lithium battery using this composite electrolyte shows a specific capacity of 140mAhg −1 and an unprecedentedly high capacity retention of 83% after 500 cycles at 60 °C and the rate of 1C. It is concluded that good electrode/electrolyte interfacial stability and contact as well as fast Li ion conductivity obtained by the addition of active garnet particulates to PEO/LiClO4 matrix are essential criteria for good charge/discharge performance of all-solid-state lithium batteries.